Applying Technology Acceptance Model Towards Cashless Payment Usage Among Consumers in Kulai, Johor - Lew, Mei Mei; Atan @ Yaakub, Siti Anisah (Research in Management of Technology and Business, 2021)
Cashless payments is becoming popular and accepted in Malaysian consumers. In the market, there are some types of cashless payment for example, plastic cards, e-wallet, electronic transfers, and online banking. Each type of the cashless payment may have its own advantages and disadvantages. Among the disadvantage of cashless payment like e-wallet is security. The purpose of this research was to study the factors of cashless payment usage among consumers in Kulai, Johor. Technology Acceptance Model (TAM) framework was used as variable factors which were perceived usefulness, perceived ease of use, perceived risk and trust, to measure factors towards cashless payment usage among consumers in Kulai, Johor. This study used online questionnaire to collect data from respondents. 734 questionnaires were distributed to the respondents and a total of 205 sets has been returned back. The results showed that all the studied variables have a positive relationship with cashless payment usage. This research can contribute some idea to the cashless payment service provider firms to provide a more customers oriented services.